The entry of international CPA firms into emerging markets: motivational factors and growth strategies - Kirsch, Robert J; Laird, Kenneth R; Evans, Thomas G (The International Journal of Accounting, 2000)
This article examines the entry of professional service firms, specifically the Big Six international accounting firms, into emerging foreign markets and explores how they develop and expand their business once established in those markets. The study is based on survey data (supplied by the Big Six) regarding their penetration of the People's Republic of China, the Commonwealth of Independent States, and Central Europe. A conceptual model is employed to illustrate the interrelationship between a firm's specific characteristics, the foreign environment, and foreign subsidiary intrafirm structure. Growth potential, client needs, favorable political/legal climate, and cultural considerations emerged as important factors in determining market entry and growth strategies for professional services firms. The research findings broaden our understanding of factors that influence professional services firms' development of pricing and marketing mix strategies. While all firms surveyed offered a full range of services, their marketing mix strategy differed from domestic approaches because of various local constraints on pricing and promotion. Copyright © 2000 University of Illinois.
Keywords: Commonwealth of independent States; Eastern European and Baltic States; International market entry and expansion; International marketing of accounting services; Marketing mix strategies of professional services firms; People's Republic of China; dept.acc; dept.mkt